Associations between dietary copper intake, general obesity and abdominal obesity risk: A nationwide cohort study in China - Wang, Weiqi; Liu, Lin; Shan, Ruiqi; Wang, Changhong (Frontiers in Nutrition, 2022)
Objective: Copper plays a crucial role in redox reactions. The aims of this research are to examine the effects of copper consumption on general obesity and abdominal obesity risk. Methods: Overall, data of 13282 participants were obtained from the China Health and Nutrition Survey (1997–2011). A combination of individual 24-hour recall and household survey was used to assess dietary intake. Time-dependent mixed effect Cox regression model treating family as a random effect were used to assess the associations between quintiles of copper intake, general obesity and abdominal obesity risk. Obesity was defined by BMI ≥ 28 kg/m2, and abdominal obesity was defined as waist circumference ≥85 cm in men and ≥80 cm in women. Results: During follow-up, 1073 and 4583 incident cases of general obesity and abdominal obesity occurred respectively. There were U-shaped associations of dietary copper intakes with general obesity and abdominal obesity (P for nonlinearity <0.001). In the general obesity track, compared with quintile 3 (reference category), participants in the top quintile and bottom quintile showed higher general obesity risk (HR, 2.00; 95%CI: 1.63, 2.45 for the top quintile, HR, 1.34; 95%CI: 1.08, 1.68 for the bottom quintile). In the abdominal obesity track, compared with quintile 3, the top quintile and bottom quintile were also associated with a significantly increased risk of abdominal obesity (HR, 1.68; 95%CI: 1.52, 1.87 for the top quintile, HR, 1.36; 95%CI: 1.22, 1.52 for the bottom quintile). Conclusions: We demonstrated U-shaped associations between dietary copper, general and abdominal obesity risk in Chinese and emphasized the importance of maintaining appropriate copper intake level for the prevention of obesity.